Genocide – interpretation of concept in Lithuania and abroad - Žilinskas, Justinas (Genocidas ir rezistencija, 2025)
While discussing various issues related to interpretation of genocide from historical, moral and political perspectives, it is impossible not to address the legal issues, because genocide is not a just an occurrence – it is first and foremost one of the most serious international crimes against humanity. The legal aspect is all the more important given that the unambiguity, precision, specificity and uniformity of the legal wording have a major impact on the possibility of bringing perpetrators to justice; bringing the wording in line with global practice leads to more effective cooperation and guarantees and ensures assistance in investigating one or other case. Therefore, we would like to present a small comparative analysis on the approach to genocide in the Lithuanian legal system and how it is perceived in international law, wherefrom the concept of genocide originated.
Keywords: genocide; Lithuania law; international law; penal code